Performance management systems: Reviewing the rise of dynamics and digitalization - Jonatan Sahlin; Jannis Angelis (Cogent Business & Management, 2019)
Purpose: Given the rise of big data and use of analytics, this study explores how the performance measurement systems research field has incorporated dynamic aspects and digitalization prevalent in rapidly changing and competitive environments. Design/methodology/approach: In the study we conduct a software supported and iterative systematic literature review of the performance management field together with a keyword network analysis. The meta-analysis provided a quantitative method that identified gaps and directions. Findings: The findings suggest there is a link between performance measurement systems and dynamics, but the link is weak, and the main research does not incorporate dynamic elements. There is an observable research community interest in managing information for informed decisions through digitalization. However, two broad research perspectives on performance management systems in highly dynamic and competitive environments were identified, one group exploring dynamic conditions, and the other digital technologies and optimization. Researchers positioning themselves in the dynamic subgroup are likely take an organizational or human capital perspective when exploring applications of performance management systems, while the other group mainly pursues research within artificial intelligence, automatization, and optimization. There is limited research with coverage of both groups, highlighting a notable gap in the existing research. Practical implications: The study presents several identified gaps within performance management systems and dynamic environments to be addressed with further empirical research. In addition, k-core analysis presented a conceptual context to position future research. Continued research will help managers develop performance measurement systems, based on real-time data, that move synchronously with the rapidly changing environment rather than maintaining inert systems that might adversely affect performance. Originality/value: This paper contributes to the understanding of performance measurement and management research in dynamic and digital environments.
Keywords: 650; dynamic; performance management systems; algorithmic management; digitalization